2010
DOI: 10.1080/20786204.2010.10874046
|View full text |Cite
|
Sign up to set email alerts
|

Validating that palliative care giving is a stressful occupation: the case of the Kanye community home-based care programme, Botswana

Abstract: Background: It remains an incontrovertible fact that the phenomenon of HIV/AIDS has not only posed major health and development challenges, but is also a stressor experienced at local, regional and global levels. This article explores the stressrelated challenges facing volunteer palliative caregivers in the Kanye community home-based care (CHBC) programme. Methods:The study was explorative in nature and qualitative in design, and used convenience sampling methodologies to involve 82 registered primary caregiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 6 publications
2
19
0
Order By: Relevance
“…Qalinge [23] study found that most caregivers had low levels of education requiring continuous in service training, not just on long intervals, to enable the caregivers though of low literacy levels to grasp the basic skills of writing or understanding the interpretation of dosses of the medication for specific patients they care for. Cameroon et al [24] has recommended that community care givers be fully trained in home care, palliative care, infection control, psychosocial counselling and proper record keeping in order to improve their work outcome Psychosocial challenges Stress and burnout A study done in Choma among home based care givers [25] found the levels of work related stress to be at 35.6% which compares well with this study, which found the stress levels to be at 56.3%. This could be speculated to be due to various reasons like family rejection and neglect, negative attitude of the patient towards the counsel and medication that is being provided among other reasons which could lead to work burnout.…”
Section: Lack Of Health Kits and Training Supportsupporting
confidence: 60%
“…Qalinge [23] study found that most caregivers had low levels of education requiring continuous in service training, not just on long intervals, to enable the caregivers though of low literacy levels to grasp the basic skills of writing or understanding the interpretation of dosses of the medication for specific patients they care for. Cameroon et al [24] has recommended that community care givers be fully trained in home care, palliative care, infection control, psychosocial counselling and proper record keeping in order to improve their work outcome Psychosocial challenges Stress and burnout A study done in Choma among home based care givers [25] found the levels of work related stress to be at 35.6% which compares well with this study, which found the stress levels to be at 56.3%. This could be speculated to be due to various reasons like family rejection and neglect, negative attitude of the patient towards the counsel and medication that is being provided among other reasons which could lead to work burnout.…”
Section: Lack Of Health Kits and Training Supportsupporting
confidence: 60%
“…In Botswana, this task has been achieved perfectly well with the government institutionalizing the community home based care programmes to operate within the mainstream health care systems. [3–6] However, even with this community goodwill, skewed gender phenomenon is glaring, with women largely volunteering to shoulder care and support to the people living with HIV/AIDS more than men. This has been worrying, making it difficult to take stock of the country’s success to Millennium Development Goal number three of the envisaged global gender equality, and eradicating gender retrogressive attitudes and stereotypes towards the role and place of women in the societies.…”
Section: Problem Statementmentioning
confidence: 99%
“…Men are still operating behind the patriarchal curtains or lenses to shun or justify their non performance in terms of care giving. [6923]…”
Section: Factors Besetting Male Involvement In Caregivingmentioning
confidence: 99%
See 2 more Smart Citations